2019
DOI: 10.1002/sono.12187
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, risks, underlying mechanisms, preventative guidelines, and interventions of sonographer work‐related injuries: A literature review

Abstract: Work‐related injuries (WRIs) in sonographers are concerning for sonographers and their employers. This review synthesised published guidelines, recommendations, and research relating to the prevalence, risks, underlying mechanisms, and preventative interventions of sonographer WRIs to improve understanding of the existing evidence and knowledge gaps in this area. Seventy articles published between 1985 and 2018 were identified and reviewed. Sonographer WRIs are very prevalent.Monitoring of prevalence should co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…This study found a prevalence of work-related musculoskeletal pain in a majority of sonographers and at a much higher rate than their peers (86% vs 46%). Similar to other studies (Friesen et al, 2006;Pike et al, 1997;Russo et al, 2002;Seto & Biclar, 2008;Tinetti & Thoirs, 2019), the findings from Barros-Gomes and colleagues (2019) report the neck, shoulder, lower back, and hand as the most common sites for sonographer discomfort. It is important to note that sonographers missed work, had work restrictions, and considered changing employment more often than their peers (Barros-Gomes et al, 2019).…”
Section: Ergonomic Risk In Sonographysupporting
confidence: 83%
See 1 more Smart Citation
“…This study found a prevalence of work-related musculoskeletal pain in a majority of sonographers and at a much higher rate than their peers (86% vs 46%). Similar to other studies (Friesen et al, 2006;Pike et al, 1997;Russo et al, 2002;Seto & Biclar, 2008;Tinetti & Thoirs, 2019), the findings from Barros-Gomes and colleagues (2019) report the neck, shoulder, lower back, and hand as the most common sites for sonographer discomfort. It is important to note that sonographers missed work, had work restrictions, and considered changing employment more often than their peers (Barros-Gomes et al, 2019).…”
Section: Ergonomic Risk In Sonographysupporting
confidence: 83%
“…Sonographers must apply pressure to the transducer to maintain contact with the patient throughout the procedure (Murphey, 2017). In a review of the literature it has been found that postural risk factors for sonographers include shoulder abduction and flexion, wrist deviation and flexion, and bending/twisting of the trunk and neck (Tinetti & Thoirs, 2019). These postures arise as sonographers attempt to operate the transducer and the computer simultaneously while navigating around the patient and the bed.…”
Section: Ergonomic Risk In Sonographymentioning
confidence: 99%
“…Previous studies dedicated to diagnostic radiographers showed a prevalence ranging from 67% [ 3 ] to 93% [ 2 ] of WRMSDs with back, neck and upper limbs, as the most affected anatomical regions [ 3, 7 ]. In other imaging specialties such as sonography, radiographers showed to be particularly exposed to several risk factors with a prevalence of WRMSDs over 90% [ 4 ]. The neck, shoulder, and wrist/hand are the most affected anatomical areas [ 8, 9 ], notably due to specific wrist and body movements during the ultrasound scanning [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Radiographers are amongst health professionals presenting a high prevalence of WRMSDs symptoms [2][3][4]. However, prevalence, and symptoms are slightly dependent on the type of studies and imaging modalities that are assessed [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Work-related musculoskeletal disorders (WRMSDs) are frequently observed in radiographers (Daniel et al, 2018), however, prevalence, and symptoms are slightly dependent on studies and imaging modalities included (Griffin, 2018;Lorusso et al, 2007;Pompeii et al, 2008;Siewert et al, 2013;Tinetti & Thoirs, 2019). Previous studies dedicated to diagnostic radiographers showed a prevalence of WRMSDs symptoms ranging from 67% (Lorusso et al, 2007) to 93% (Daniel et al, 2018) with back, neck and upper limbs as the most affected anatomical regions (Bright Ofori-Manteaw et al, 2015;Kumar et al, 2004b;Lorusso et al, 2007).…”
Section: Introductionmentioning
confidence: 99%